Alive Library Sebagai Brand Positioning di Perpustakaan Sekolah Bina Persada - Sugara, Septian; Rusmono, Doddy; Agustina, Susanti (Edulib, 2016)
Abstract. This research is motivated by the phenomenon of brand positioning implementation as a superiority at Perpustakaan Sekolah Bina Persada, which effectively increase the sense of belonging and users interest. Approach used in this research was case study qualitative. The data were collected by observation, interview and study of documentation. The findings of the research are : (1) alive library as brand positioning at Perpustakaan Sekolah Bina Persada is motivated by librarian’s concern of students’ visit restriction. (2) implementation of brand positioning at Perpustakaan Sekolah Bina Persada is generally successful, although the implementation hasn’t fitted the theory. (3) pattern of alive library brand positioning implementation, which has a possibility to be a model of implementation at another (school) library.Keyword : alive library, brand positioning, school library, librarian.        Abstrak . Penelitian ini dilatarbelakangi oleh fenomena implementasi brand positioning sebagai suatu keunggulan di Perpustakaan Sekolah Bina Persada yang mampu meningkatkan sense of  belonging dan minat kunjung pemustaka. Penelitian ini menggunakan pendekatan kualitatif studi kasus. Teknik pengumpulan data dilakukan dengan observasi, wawanara dan studi dokumentasi. Temuan hasil penelitian mencakup: (1) alive library sebagai brand positioning di Perpustakaan Sekolah Bina Persada dilandasi oleh keprihatinan Pustakawan terhadap pembatasan waktu kunjungan siswa ke perpustakaan. (2) implementasi brand positioning di Perpustakaan Sekolah Bina Persada dapat dikatakan berhasil, meskipun pada penerapannya belum sesuai dengan teori. (3) pola implementasi brand positioning alive library yang dapat menjadi model untuk diimplementasikan di perpustakaan (sekolah) lainnya.Kata kunci : alive library, brand positioning, Perpustakaan Sekolah, Pustakawan.